Soybean Cost-Return Budget in South Central Kansas - Dhuyvetter, Kevin C.; Duncan, Stewart R. (My University, 2001)
This publication provides estimated cost and returns for forward farm planning for soybeans in south central Kansas.
MF2156_2001_10
Keywords: MF2156; Crops; Economics; MF